Ibuprofen inhibits colitis-induced overexpression of tumor-related Rac1b - Matos, Paulo (2013)
The serrated pathway to colorectal tumor formation involves oncogenic mutations in the BRAF gene which are sufficient for initiation of hyperplastic growth but not for tumor progression. The analysis of colorectal tumors revealed that overexpression of splice variant Rac1b occurs in around 80% of tumors with mutant B-Raf and both events were shown to cooperate in tumor cell survival. Here we provide evidence for increased expression of Rac1b in samples from inflammatory bowel disease patients as well as following experimentally induced colitis in mice. The increase of Rac1b in the mouse model was specifically prevented by the non-steroidal anti-inflammatory drug ibuprofen, which also inhibited Rac1b expression in cultured HT29 colorectal tumour cells through a cyclooxygenase inhibition-independent mechanism. Accordingly, the presence of ibuprofen led to a reduction of HT29 cell survival in vitro and inhibited Rac1b-dependent tumor growth of HT29 xenografts. Together, our results suggest that stromal cues, namely inflammation can trigger changes in Rac1b expression in the colon and identify ibuprofen as a highly specific and efficient inhibitor of Rac1b overexpression in colorectal tumors. Our data suggest that the use of ibuprofen may be beneficial in the treatment of patients with serrated colorectal tumors and in cancer prophylaxis following colon inflammation disorders.